W KWESTII AKTUALNEGO STANU DYSKUSJI O POJĘCIU DOBRA PRAWNEGO - Hirsch, Hans Joahim (Wydział Prawa i Administracji UAM, 2002)
It is legitimate to talk about a decrease in popularity of the view that the scope of criminal law is set out and limited by the legal goods that are previously selected for it. The notion of a legal good is not the actual element determining the borderlines previously drawn for the criminal law. Penalty and the scope of its national legitimacy can only play this role. However, the notion of legal good is significant in the form of its systemically immanent function within the positive law. This argument is sill dominant, since the arguments in favour of it appear convincing enough. However, the usefulness of this notion is threatened by the current tendency to dissolve it, especially within the interpretation of the new criminal law regulation. This dematerialisation phenomenon does not discard partly or completely the notion of systemically immanent legal good. Instead, it challenges science to make an attempt at redefining or reformulating the directives of applying and verifying specific regulations, and possibly also criticising them.
ON THE CURRENT CONDITION OF THE DEBATE OVER THE NOTION OF LEGAL GOOD